DIY for renters : don't call the landlord : a renter's guide to repairs and personalizations that won't break your lease - Byers, Charles, 1959- (Creative Homeowner, 2020)
"DIY for Renters shows how to perform common repairs and upgrades that are economical, safe, and do not conflict with tenant/landlord agreements. Learn how to deal with all of the normal maintenance issues that every home encounters, from squeaky doors and wet basements to plumbing, heating and electrical repairs"--